Izdiwajiyatul Lughah dan Problematikanya dalam Pembelajaran Bahasa Arab - Mubarak, Faisal; Muradi, Ahmad; Rahman, Ahmad Abdul (Shaut al Arabiyyah, 2021)
Diglossia in Arabic Language is a problem faced by language learners. It’s apparent from the difficulties learners when finding a different from the Arabic language between what they learn in the classroom with what is on the outside of the classroom. This situation can be seen with the two regional variations of formal (fushah) and non-formal (ammiyah). Variety of formal (fushah) language used in official places like school, university, office and other government agencies.